Improvement of lipase activity by synergistic immobilization on polyurethane and its application for large-scale synthesizing vitamin A palmitate. Issue 5 (28th May 2019) - Cui, Caixia; Li, Linjing; Li, Mingjie
Abstract: We have developed an improved and effective method to immobilize lipase on hydrophobic polyurethane foam (PUF) with different modifications. PUF was treated with hydrochloric acid to increase the active sites and then the active carboxyl groups and amino groups were exposed. Enzyme activity of lipase immobilized on PUF-HCL (8000 U/g) was 50% higher than that of lipase immobilized on PUF (5300 U/g). There is an increase in the activity of the immobilized lipase on AA/PEI-modified support (115, 000 U/g), a 2.17-fold increase compared to lipase immobilized on the native support was observed. The activity of immobilized lipases was dependent on the PEI molecular weight, with best results from enzyme immobilized on PUF-HCL-AA/PEI (MW 70, 000 Da, 12, 800 U/g)), which was 2.41 times higher compared to that of the same enzyme immobilized on PUF. These results suggest that the activity of immobilized lipase is influenced by the support surface properties, and a moderate support surface micro-environment is crucial for improving enzyme activity. Finally, the immobilized lipase was used for the production of vitamin A palmitate. The immobilized lipase can be reused for up to 18 times with a conversion rate above 90% for 12 h in a 3 L bioreactor. Research highlights: An efficient immobilization protocol on polyurethane foam was developed Polyethyleneimine and acetic acid were used to regulate the micro-environment concurrently The activity of lipase immobilized on PUF-HCL-AA/PEI was improved by 2.41 times Immobilized lipase exhibited excellent operational stability for vitamin A palmitate synthesis